The Penultimate Glacial Termination and Variability of the Pacific Intertropical Convergence Zone. Issue 9 (13th May 2019) - Reimi, M. A.; Marcantonio, F.; Lynch‐Stieglitz, J.; Jacobel, A. W.; McManus, J. F.; Winckler, G.
Abstract: Understanding how the Intertropical Convergence Zone (ITCZ) responds to abrupt climate change is essential for reconstructing large‐scale atmospheric circulation across climate transitions. However, key differences between dynamical models and observational constraints on ITCZ movement remain unresolved. Here, we examine the Pb and Nd radiogenic isotope signatures of dust deposited in the central equatorial Pacific (CEP) from 160 to 105 kyr. We quantified the relative contributions of Northern Hemisphere‐ and Southern Hemisphere‐sourced dust to the CEP. In contrast with previous model estimates, we demonstrate that South America is an important source of dust to the CEP during glacial periods. Our new observations provide a critical data set for verifying dynamical arguments about tropical hydroclimate. We infer that the southernmost position of the ITCZ precipitation centroid occurs between 136 and 131 kyr, coincident with the timing of North Atlantic Heinrich Stadial Event 11 (136 to 129 kyr). Plain Language Summary: In this study we investigate the changes in dust origin to the Central Equatorial Pacific that happened between 160 and 105 kyr before present. This time period is interesting because it includes the end of an ice age which terminated between 136 and 129 kyr. This transitional period was long enough to allow us to look at changes in dust sources as the ice age was ending. We used changes in the chemistry of the dust fraction found in marine sediments and calculated what percentage of this dust originated in the Northern and the Southern Hemispheres. We found that more dust originated in South America than was previously thought. We also found that the dust pattern deposited across out sites suggests that the dominant tropical hydroclimate feature, coincident with the thermal equator, was south of its modern position during the ice age and that it traveled further south during the transition from cold to warm conditions, finally settling near its modern position once the climate transition was complete. Key Points: We analyzed the dust provenance of central tropical Pacific sediments South American contribution to Central Pacific sediments is larger than previously thought The southernmost position of the ITCZ coincides with Heinrich Stadial Event 11